Improving The Motivation and Learning Outcomes Students with Applying “Everyone Is Teacher Here” Learning Method - Eko Triatmojo Wibowo; Yuli Agustina (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
This research aims to know the improvement of learning outcome and learning motivation of students by using Everyone Is Teacher Here learning method. This research was included into Classroom Action Research which conducted on 2 cycles in which each cycle consists of 2 meetings and 4 stages. The12th Grade of Office Administration SMK PGRI 6 Malang for 27 students as research subject. Data of learning outcome obtained from post-test and data of student learning motivation obtained from questionnaire. The research result showed average score of cognitive and affective learning outcome was increase significantly as well as student learning motivation in the category of very satisfying. The research result explained that Everyone Is Teacher Here learning method proven to improve learning outcome and learning motivation of students. It is suggested to the teachers to apply this method, especially to the active learning focuses on student.